Construction of an In2O3/Bi2S3 Z-Scheme Heterojunction for Enhanced Photocatalytic CO2 Reduction - Sun, Miaofei (Langmuir : the ACS journal of surfaces and colloids, 2024)
Photocatalytic conversion of CO2 to hydrocarbon fuel is a potential strategy to solve energy shortage and mitigate the greenhouse effect. Here, direct Z-scheme heterojunction photocatalysts (In2O3/Bi2S3) without an electron mediator are prepared by a simple hydrolysis method. The In2O3/Bi2S3 composite photocatalysts show greatly boosted photoactivity on CO2 conversion to CO compared with the pristine In2O3 and Bi2S3. The highest CO evolution rate of 2.67 μmol·g-1·h-1 is achieved by In2O3/Bi2S3-3, without any sacrificial agent or cocatalyst, which is about 3.87 times that of In2O3 (0.69 μmol·g-1·h-1). The boosted photocatalytic performance of In2O3/Bi2S3 composite catalysts can be ascribed to the establishment of a Z-scheme heterojunction, improving the photoabsorption and facilitating charge separation and transfer. This study provides a reference for designing and fabricating high-efficiency Z-scheme heterojunction photocatalysts for photocatalytic CO2 reduction